Livestock production systems - Wilson, R. Trevor (Macmillan Education, 1995)
Forms part of a series of 15 books on animal production in the tropics, which are intended to provide up-to-date information for students, extension specialists and farmers, in an accessible manner. The book explains why livestock are an important component of agriculture in the tropics.